Psychological and Environmental Support: An Important Complement to Controlled Antiretroviral Therapy for HIV Patients - Setiyo Budi Santoso; Heni Lutfiyati; Ulfahishofi Hanifah Afifi; Shellyta Ratnafuri (Konsorsium LPPM Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2021)
This article presents a quality of life profile for HIV patients who have undergone controlled antiretroviral therapy. Specifically, researchers reviewed the unique needs of research subjects for psychological and environmental support. The research took place at the Regional General Hospital KRT Setjonegoro Wonosobo, involving 68 research subjects. All study subjects were HIV patients undergoing controlled antiretroviral therapy (outpatient) with a duration of more than six months and were aged more than 15 years. Investigation of the quality of life profile used the Indonesian version of the WHOQOL-HIV Bref questionnaire. The results showed that HIV patients who underwent controlled therapy had a higher quality of life score than general HIV patients. Antiretroviral treatment has helped them have physical qualities, independence, spiritual side, and social abilities in living life. Even so, they need psychological intervention and environmental support to have consistent quality of themselves. Health workers involved in managing HIV patients need to provide professional interventions to improve their ability to concentrate and ensure that they are always comfortable with their physical condition. Further, there is a need for cooperation by relationships (family, friends, community) and health workers to ensure that HIV patients do not experience financial difficulties, enjoy time in a relaxed manner, and feel safe as part of the environment society in general.